Implementation of Cooperative Learning Through Crossword Puzzle Strategy to Increase the Motivation of Grade 5 Students - Pancahadi Siswasusila (Madrosatuna: Journal of Islamic Elementary School, 2017)
The emergence of unpleasant assumptions about Islamic religious education, such as Islam is taught more on memorization that must be practiced. So the problem that is often encountered in teaching, especially teaching Islam is how to present material to students well so that the results are effective and efficient. In order for the learning of Islamic religious education (pendidikan agama Islam/PAI) on the material of the names of the books of God to be embedded in students well, then many concepts of active learning models are offered. One of them is by implementing a cooperative learning model through the crossword puzzle strategy that is expected to increase students' learning motivation. By involving them actively in the learning process, students will experience or even discover science independently. The purpose of this study was to describe the implementation of cooperative learning through the crossword puzzle strategy in increasing learning motivation in the Grade 5 PAI Subjects of Jombatan 1 Elementary School in Jombang Regency. The research method used is action research. In collecting data, the author uses the observation method, checklist, and participatory methods. The results of the study show that the implementation of cooperative learning through crossword puzzle strategies is effective in increasing the motivation to learn PAI subjects. This can be seen from the enthusiasm of students in working on group puzzles in PAI learning about the names of God's books. And learning that had been stiff and boring had become more alive because educators directly involved students in learning, not only listening, seeing and working on the questions given. Having been well implemented and in accordance with existing learning concepts, this could also be seen from the preparation, implementation (an application) and evaluation carried out in well-designed teaching and learning activities.